2011
DOI: 10.4236/health.2011.312125
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric measurements at birth as predictor of low birth weight

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
13
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 13 publications
6
13
1
Order By: Relevance
“…Few studies 2,[11][12][13] have been done to find out a relationship between the birth weight and anthropometric parameters to predict birth weight. In this study chest circumference showed the high correlation (r=0.752) with abdominal circumference as compared to other anthropometric parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies 2,[11][12][13] have been done to find out a relationship between the birth weight and anthropometric parameters to predict birth weight. In this study chest circumference showed the high correlation (r=0.752) with abdominal circumference as compared to other anthropometric parameters.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in 2011 reported that the optimum cut-off point for MUAC/ head circumference ratio is 0.303 [18] which indicate wasting. However, in this study majority (62%) of the neonates had a ratio of ≥0.303.…”
Section: Figure 2: Maternal Haemoglobin Before Delivery (N=202) and Amentioning
confidence: 99%
“…The anthropometric measurements that have been studied include; body length, foot length, head, chest, thigh, calf and mid-upper arm circumference [8-12]. Generally studies show that choice of a suitable anthropometric measure is context-specific.…”
Section: Introductionmentioning
confidence: 99%
“…Generally studies show that choice of a suitable anthropometric measure is context-specific. Various studies recommend using specific measures including head circumference [9], chest circumference [8,13], mid upper arm circumference [14,15], thigh circumference [10,16], foot length [17] and calf circumference [12,18] as the most appropriate. Even where the same measure was recommended the cut-off points varied for different contexts e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation